Produção in vitro de embriões bovinos: uso da glutationa durante o processo de lavagem e capacitação espermática - ANDREOTI, Magna (Universidade Federal do Pará, 2013)
The aim of this work was evaluated the effect of Glutathione addition (GSH – 0.3mg/mL) in the semen separation, washing and capacitation steps on the bovine in vitro embryo production. Semen from one only bull was separated with Percoll and centrifugated twice with in vitro fertilization (IVF) medium (washing). Spermatozoa were capacitated in IVF medium during 1 h in 5% CO2 incubator at 38,5ºC. Experimental groups were: Control – it was not supplemented with GSH in separation and washing and capacitation was excluded; Group 1: without GSH in all steps; Group 2: GSH supplementation just in the capacitation; Group 3: GSH supplementation in the separation and washing steps (first washing only); Group 4: GSH supplementation in all steps. Bovine oocytes collected at slaughterhouse were in vitro matured and fertilized after semen preparations. Embryos were cultured during seven days with cleavage being analysed at day 2 and blastocyst rates and total embryo cell number (quality) at day7. Embryo rates were evaluated with chi-square test (χ2) and embryo quality with ANOVA in the software Bio Estat 3.0 (AYRES, et al., 2003) at significance level of 5%. There was not effect of the GSH supplementation in different steps of semen preparation (p>0,05) on cleavage, blastocysts and hatching rates (Control Group: 52%, 35% and 50%, respectively; G1: 60%, 37% and 44%, respectively; G2: 57%, 40% and 50%, respectively; G3: 56%, 37% and 51%, respectively; G4: 47%, 30% and 48%, respectively). Moreover, it was not observed effect on mean (±SD) of embryo total cell number (Control: 30,9±21,87, Group 1:57,8 ±18,26; Group 2:66,2 ±20,14; Group 3:62,1 ±22,48; Group 4:76,7 ±29,28; p> 0,05).